Can an Intensive Diet and Exercise Program Prevent Knee Pain Among Overweight Adults at High Risk?. Issue 7 (July 2015) - White, Daniel K.; Neogi, Tuhina; Rejeski, W. Jack; Walkup, Michael P.; Lewis, Cora E.; Nevitt, Michael C.; Foy, Capri G.; Felson, David T.; for the Look AHEAD Research Group
<x xml:space="preserve">Abstract</x> Objective It is unclear whether an intensive program of weight loss combined with exercise prevents the onset of knee pain among those at high risk. We examined whether an intensive lifestyle intervention (ILI) prevents incident knee pain compared with a diabetes mellitus support and education (DSE) comparison group among overweight adults with diabetes mellitus. Methods We conducted a secondary analysis of the Action for Health in Diabetes (Look AHEAD) study, which is a randomized intervention trial of adults who were obese and had type 2 diabetes mellitus starting in 2001. We studied a subcohort of 2, 889 subjects who reported no knee pain at baseline but were at high risk due to obesity. Risk ratios (RRs) were calculated to examine the association of ILI versus DSE with incident knee pain at year 1 and year 4. All analyses were adjusted for potential confounders. Results Age, sex, and body mass index were similar among ILI and DSE participants with no knee pain at baseline. At year 1, ILI participants were 15% less likely to develop knee pain compared with DSE participants (RR 0.85, 95% confidence interval 0.74–0.98). At year 4, this difference decreased to 5% and was no longer statistically significant. Conclusion An ILI of diet and exercise may prevent the development of knee pain among those at high risk in the short term. Health care providers may consider recommending diet and exercise as a means to prevent the development of knee pain among those at high risk.